2010
DOI: 10.1088/2041-8205/720/1/l82
|View full text |Cite
|
Sign up to set email alerts
|

THE GEMINI NICI PLANET-FINDING CAMPAIGN: DISCOVERY OF A CLOSE SUBSTELLAR COMPANION TO THE YOUNG DEBRIS DISK STAR PZ Tel

Abstract: We report the discovery of a tight substellar companion to the young solar analog PZ Tel, a member of the β Pic moving group observed with high contrast adaptive optics imaging as part of the Gemini NICI Planet-Finding Campaign. The companion Myr for the system, we estimate a mass of 36±6 M Jup based on the Lyon/DUSTY evolutionary models. PZ Tel B is one of few young substellar companions directly imaged at orbital separations similar to those of giant planets in our own solar system. Additionally, the primar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 49 publications
4
118
3
Order By: Relevance
“…Some objects were nonetheless discovered (e.g. Lafrenière et al 2008;Thalmann et al 2009;Biller et al 2010), demonstrating that these objects exist, but are indeed rare (Nielsen & Close 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some objects were nonetheless discovered (e.g. Lafrenière et al 2008;Thalmann et al 2009;Biller et al 2010), demonstrating that these objects exist, but are indeed rare (Nielsen & Close 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Lagrange et al 2010;Marois et al 2010;Carson et al 2013;Kuzuhara et al 2013;Rameau et al 2013b) and brown-dwarf companions (e.g. Thalmann et al 2009;Biller et al 2010). However, the published imaging surveys have largely avoided close binary targets, leaving a vast unexplored territory in the parameter space of circumbinary planets.…”
Section: Introductionmentioning
confidence: 99%
“…The total mass was estimated to be 0.1095 ± 0.0022 M (Dupuy & Liu 2011) and the age 0.93 Gyr. PZ Telescopii B is a BD companion with a mass of 24-40 M Jupiter at a projected separation of ∼15 AU (Biller et al 2010;Mugrauer et al 2010). It is a member of the β Pic moving group.…”
Section: Datasetmentioning
confidence: 99%
“…Other than a few planets (e.g., Kuzuhara et al 2013;Rameau et al 2013b) and brown dwarfs (BDs; e.g., Chauvin et al 2005b;Biller et al 2010;Mugrauer et al 2010;Wahhaj et al 2011;Carson et al 2013) detected, many surveys found no planetary companions. The null results cannot be used to fit power-laws to the planetary distributions beyond 10 AU.…”
Section: Introductionmentioning
confidence: 99%